Sex differences in response to stress and expression of depressive-like behaviours in the rat. - Dalla, Christina; Pitychoutis, Pothitos M; Kokras, Nikolaos; Papadopoulou-Daifoti, Zeta (Curr Top Behav Neurosci, 2011)
Women are more susceptible than men to certain stress-related psychiatric disorders, such as depression. Preclinical studies aim to understand these sex differences by studying male and female rats in stress models. In this chapter, we review sex differences in behavioural aspects, as well as neurochemical and neurobiological findings derived from acute, repeated and chronic stress models. In particular, we focus on sex differences in depressive-like symptomatology expressed in the forced swim test, the chronic mild stress (CMS) and the learned helplessness models, the Flinders Sensitive Line rats (FSL), which is a genetic model of depression and in the lipopolysaccharide (LPS)-induced sickness behaviour, a putative inflammatory model of depression. Also, sex differences in stress effects on learning and memory parameters are discussed, because cognitive alterations are often seen in sex-differentiated psychiatric disorders. The observed behavioural alterations are often linked with abnormalities in the endophenotype, such as in hormonal, neurochemical, immune and neuroplasticity indices. From these data, it is clear that all stress models have strengths and limitations that need to be recognized in order to use them effectively in the investigation of sex differences in affective disorders.
Keywords: Animals; Depression; Disease Models, Animal; Female; Learning; Male; Neurosecretory Systems; Rats; Sex Characteristics; Stress, Psychological; Time Factors